Innovation of Regional Tax Revenue: The Integration of TMD and MPOS in Improving Hotel Tax Efficiency - Rahman, Rahman; Liwaul, Liwaul; Amir , Muhammad (Jurnal Administrasi Publik (Public Administration Journal), 2025)
Increasing efficiency and transparency in local tax management is a significant challenge for many local governments, especially in developing cities. The study aims to explore the application of the Transaction Monitoring Device (TMD) and Mobile Payment Online System (MPOS) in the hotel tax sector of Kendari City, as well as to identify the impact of this technology on tax administration efficiency and regional revenue optimization. The method employed in this study is a qualitative descriptive approach, utilizing data collection through in-depth interviews, documentary studies, and field observations. The study results indicate that implementing TMD and MPOS enhances tax collection efficiency, improves transaction data accuracy, and fosters taxpayer compliance. Hotel tax revenues exceeding the yearly target show that this technology optimizes regional tax revenues. Employees also play an essential role in supporting the smooth implementation of these two systems by improving internet infrastructure and training taxes. This research implies that digital-based technology can accelerate and simplify regional tax management, increase taxpayer confidence, and support regional economic growth. The limitation of this study is that it is limited to the hotel tax sector in Kendari City and does not examine other external factors that affect tax revenue. Further research is recommended to explore different industries and broader policy factors when applying this technology.